KOHESI DAN KOHERENSI WACANA LAGU DALAM ALBUM JKT48 HEAVY ROTATION - Diah Ayu Kartikasari (Humaniora Scientia, 2014)
This research is a study on cohesion and coherence of the song lyrics of JKT48 in the album Heavy Rotation. Cohesion and coherence play important roles to construct meaning unity of a discourse. Concerning this phenomenon, the research aims to describe and parse the  elements of grammatical and lexical cohesions as well as coherence between interlines and verse of song lyrics. This study is descriptive-qualitative in nature. The data are in the form of words, phrases, clauses, and sentences taken from the album Heavy Rotation. The songs contained within the album are ten in number. The analysis shows that cohesion and coherence found in the songs are of great  variety.  The  cohesion  used  is  of  two  kinds –grammatical  and  lexical cohesions.  Grammatical cohesion includes reference, substitution, ellipsis, and conjunction. In  fact,  personal reference, phrasal and  clausal substitution, and phoneme  ellipsis  are  greater  in  use.  Substitution  is  mostly  in  the  form  of substitution using Japanese and English rather than Indonesian. Lexical cohesion comprises repetition, synonymy, and collocation. They are used  to emphasize the important lingual units, to construct equal meaning relation, and to support the theme. Coherence is used to connect the propositions of causal relation, means- product  relation, reason-cause relation, comparison relation, setting-conclusion relation, and amplification relation. Cohesion and coherence serve to connect parts of a discourse in order to achieve a discourse which is unified, relevant, and acceptable for readers.   Key words: cohesion, coherence, song discourse, song lyrics